1998
DOI: 10.1038/31275
|View full text |Cite
|
Sign up to set email alerts
|

Histone macroH2A1 is concentrated in the inactive X chromosome of female mammals

Abstract: In female mammals one of the X chromosomes is rendered almost completely transcriptionally inactive to equalize expression of X-linked genes in males and females. The inactive X chromosome is distinguished from its active counterpart by its condensed appearance in interphase nuclei, late replication, altered DNA methylation, hypoacetylation of histone H4, and by transcription of a large cis-acting nuclear RNA called Xist. Although it is believed that the inactivation process involves the association of specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
539
3
11

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 601 publications
(582 citation statements)
references
References 25 publications
24
539
3
11
Order By: Relevance
“…MacroH2As contain an N-terminal histone H2A-like domain and a Cterminal "macro domain" of more than 200 residues that is unrelated to other histones. MacroH2A clearly contributes to gene silencing, since it is inserted into the inactive X chromosome (23,27,28) and macroH2A-containing chromatin is resistant to ATP-dependent remodeling proteins and binding of transcription factors in vitro (4).…”
Section: Description Of Sahfmentioning
confidence: 99%
“…MacroH2As contain an N-terminal histone H2A-like domain and a Cterminal "macro domain" of more than 200 residues that is unrelated to other histones. MacroH2A clearly contributes to gene silencing, since it is inserted into the inactive X chromosome (23,27,28) and macroH2A-containing chromatin is resistant to ATP-dependent remodeling proteins and binding of transcription factors in vitro (4).…”
Section: Description Of Sahfmentioning
confidence: 99%
“…MacroH2As contain an N-terminal histone H2A-like domain and a C-terminal "macro domain" of more than 200 residues that is unrelated to other histones. MacroH2A clearly contributes to gene silencing, since it is depleted from active genes, 39 inserted into the inactive X chromosome [39][40][41][42][43] and macroH2A-containing chromatin is resistant to ATP-dependent remodeling proteins and binding of transcription factors in vitro and in vivo. [44][45][46] Moreover, genetic inactivation of macroH2A1.1 and 1.2 in mice caused increased expression of some genes that are normally enriched in macroH2A1.1 and 1.2 and silenced.…”
Section: Sahf Excludes Domains Of Constitutive Heterochromatinmentioning
confidence: 99%
“…Histone macroH2A is an histone variant found enriched on inactive X chromosome of female mammals [20]. Several studies demonstrated that histone macroH2A functions both as a positive and a negative regulator of gene transcription.…”
Section: Haspin Substratesmentioning
confidence: 99%